Optimized prosthetic design, surgical technique, and cosmetic outcome in shoulder reconstruction with double-constrained implant following extra-articular shoulder resection: a proof-of-concept - Jan Lesensky; Michal Benes; Martin Havranek; Ana C. Belzarena (World Journal of Surgical Oncology)
Abstract Reconstruction of the anatomic defect following extra-articular shoulder resection is a challenging problem, particularly in cases when function of the deltoid muscle and rotator cuff are compromised. Standard reconstruction techniques often result in either instability or rigidity. Constrained implants have been used to overcome these problems; however, they have been associated with a high rate of aseptic loosening. Recently, a novel double-constrained implant has been introduced, yielding promising functional results. Nonetheless, this implant exhibited a cosmetic defect related to protrusion of the humeral component that becomes apparent with time as result of surrounding muscle atrophy. An updated improved design of the implant has been developed to counteract this. We report the case of a 15-year-old patient who underwent an extra-articular (Malawer type V) shoulder resection due to osteosarcoma and received an innovated custom-made double-constrained implant. Moreover, we describe a new modification of the Malawer utilitarian approach to the shoulder girdle that enhances tumor visibility and allows safer dissection. The patient recovered well with satisfactory outcomes at 18 months follow-up, highlighting the potential benefits of this implant design and surgical approach.